Potensi, Efektivitas Dan Kontribusi Pajak Hotel Di Kabupaten Sleman Periode 2012-2016 - Arif Triwinarso; Iwan Budiherwanto (Jurnal Solusi, 2018)
contribution to the regional economy in Sleman Regency in 2012- 2016. The data used are secondary data sourced from the Regional Financial and Asset Agency (BKAD) Sleman Regency and other official sources. The results of the study indicate the potential for hotel taxes in Sleman Regency is very large and has an upward trend year by year. The effectiveness of the potential of hotel tax with the realization of hotel tax revenue is still ineffective at an average of 44,99% per year, but the effectiveness between the target and the realization of revenue has been very effective, wich is an average of 123,50%. The contribution of hotel tax revenue to total tax in Sleman Regency is an average of 15,71%, while for Regional Original Income (PAD) an average of 9,20%.